HE0359-3959: An Extremely Radiating Quasar - Martínez-Aldama, M. L.; Del Olmo, A.; Marziani, P.; Negrete, C. A.; Dultzin, D.; Martínez-Carballo, M. A. (Frontiers in Astronomy and Space Sciences, 2017)
We present a multiwavelength spectral study of the quasar HE0359-3959, which has been identified as an extreme radiating source at intermediate redshift (z=1.5209). Along the spectral range, the different ionic species give information about the substructures in the broad line region. The presence of a powerful outflow with an extreme blueshifted velocity of -6000 kms-1 is shown in the CIV emission line. A prominent blueshifted component is also associated with the 1900A blend, resembling the one observed in CIV. We detect a strong contribution of very the low-ionization lines, FeII and Near-Infrared CaII triplet. We find that the physical conditions for the low, intermediate and high–ionization emission lines are different, which indicate that the emission lines are emitted in different zones of the broad line region. The asymmetries shown by the profiles reveal different forces over emitter zones. The high-ionization region is strongly dominated by radiation forces, which also affect the low and intermediate-ionization emitter region, commonly governed by virial motions. These results support the idea that highly radiating sources host a slim disk.